Real-Life Clinical Experience With Cariprazine: A Systematic Review of Case Studies - Csehi, Réka; Dombi, Zsófia Borbála; Sebe, Barbara; Molnár, Mária Judit (Frontiers in Psychiatry, 2022)
Background: The hierarchy of evidence coming from evidence-based medicine favours meta-analyses and randomised controlled trials over observational studies and clinical cases. Nonetheless, in the field of psychiatry, where conditions are much more complex, additional evidence coming from real-world clinical practice is necessary to complement data from these gold standards. Thus, in this systematic review, the aim is to summarise the evidence coming from clinical case reports regarding cariprazine, a third-generation antipsychotic drug that has been approved for the treatment of schizophrenia and bipolar I disorder with manic, depressive or mixed features in adults. Methods: A systematic review was performed using Embase and Pubmed databases searching for English-language cases published in peer-reviewed journals between 2000 January – 2021 September with the following search terms: (cariprazin* OR "rgh-188" OR rgh188 OR vraylar OR reagila) AND ('case report*' OR 'case report'/de OR 'case stud*' OR 'case study'/de OR 'case seri*'). Results: After the removal of duplicates, 49 articles were retrieved via the search, from which 22 were suitable for this review. These 22 articles encompassed 38 cases from which 71% described patients with schizophrenia, 16% patients with psychotic disorders, 5% patients with mood disorder and 8% described patients with other disorders such as Wernicke-Korsakoff syndrome, borderline personality disorder and obsessive-compulsive disorder with paranoid schizophrenia. The median age of patients was 31, and half of them were female. The majority of patients (76%) started cariprazine with 1.5 mg/day, and the most common maintenance dose was 4.5 mg/day (34%) and 3.0 mg/day (29%). Conclusion: Cariprazine was found to be safe and effective in a wide range of psychiatric conditions with different symptom profiles from acute psychotic symptoms through addiction to negative and cognitive symptoms. The results are in-line with the established evidence from clinical trials, however, they also show how cariprazine can be successfully utilised for treating certain symptoms irrespective of the indication.